PEMBUATAN 54 PLANG NAMA JALAN UNTUK DESA SENDAYAN DARI KUKERTA UNRI 2022: Making 54 Street Name Signs for UNRI Student Service to The Comunity - Riadi, R.M; Abdul, Aziz; Iskandar, Althaf; Putri, Angely Sundari; Lista Putri, Cindy Destia; Elisa, Desvia; Zanatha, Muhammad Kevin; Tambunan, Rafindo; Alyssa, Sarah Syafira; Daulay, Wanda Marhamah; Putri1, Widya (Dirkantara Indonesia, 2023)
Real Work Lecture is a community service program carried out in universities as a form of implementation of the Tri Dharma of Higher Education. The Real Work Lecture activity carried out by the service team for Sendayan Village is the creation of a street name sign. This flagship program is intended to help the people of Sendayan Village. This service activity begins with a request for permission and a presentation to the village head, hamlet head and all Sendayan Village staff. This activity aims to help the entire community of Sendayan Village. For an area, a street name signpost is definitely needed because it can make it easier for someone to find the location of an area and also as the identity of a residential area.